AB0924 Psychological distress symptoms and illness perceptions associated with health-related quality of life in psoriatic arthritis patients. (23rd January 2014) - Kotsis, K.; Voulgari, P.V.; Tsifetaki, N.; Machado, M.O.; Carvalho, A.F.; Creed, F.; Hyphantis, T.; Drosos, A.A.
Abstract : Objectives: Symptoms of psychological distress and illness perceptions influence outcomes in rheumatologic patients. We aimed to assess the prevalence of psychological distress symptoms and illness perceptions in psoriatic arthritis (PsA) and rheumatoid arthritis (RA) and to test whether the association between psychological variables and health-related quality of life (HRQoL) was similar in the two forms of arthritis. Methods: In 83 PsA and 199 RA patients we used the Patient Health Questionnaire (PHQ-9), the Symptom Check-List (SCL-90-R) and the Brief Illness Perception Questionnaire (B-IPQ) to assess psychological variables and the World Health Organization Quality of Life Instrument - Short-Form (WHOQOL-BREF) to assess physical HRQoL. Hierarchical regression models were built to test their independent contribution to Physical HRQoL after adjusting for demographic variables and disease parameters. Results: The prevalence of major depressive disorder as indicated by a PHQ-9 score ≥10 was 21.7% in PsA, 25.1% in RA, and 36.7% in those PsA patients with polyarthritis. After adjustment for severity of disease and pain, anxiety (b=-0.28) and concern about bodily symptoms attributed to the illness (b=-0.33) were independent correlates of physical HRQoL in PsA. In RA, depression (b=-0.29) and concern about the consequences of the arthritis (b=-0.27) were independent correlates of physical HRQoL. Conclusions: These findings suggest that psychological factors are important correlates of HRQoL in PsA, as well as in RA. Attention to patients' anxiety and their concern about numerous bodily symptoms attributed to the illness may enable rheumatologists to identify and manage treatable aspects of HRQoL in PsA. Disclosure of Interest: None Declared